A conserved GH17 glycosyl hydrolase from plant pathogenic Dothideomycetes releases a DAMP causing cell death in tomato. (11th October 2019) - Ökmen, Bilal; Bachmann, Daniel; de Wit, Pierre J.G.M.
Summary: To facilitate infection, pathogens deploy a plethora of effectors to suppress basal host immunity induced by exogenous microbe‐associated or endogenous damage‐associated molecular patterns (DAMPs). In this study, we have characterized family 17 glycosyl hydrolases of the tomato pathogen Cladosporium fulvum (CfGH17) and studied their role in infection. Heterologous expression of CfGH17‐1 to 5 by potato virus X in different tomato cultivars showed that CfGH17‐1 and CfGH17‐5 enzymes induce cell death in Cf‐0, Cf‐1 and Cf‐5 but not in Cf‐Ecp3 tomato cultivars or tobacco. Moreover, CfGH17‐1 orthologues from other phytopathogens, including Dothistroma septosporum and Mycosphaerella fijiensis, also trigger cell death in tomato. CfGH17‐1 and CfGH17‐5 are predicted to be β‐1, 3‐glucanases and their enzymatic activity is required for the induction of cell death. CfGH17‐1 hydrolyses laminarin, a linear 1, 3‐β‐glucan with 1, 6‐β linkages. CfGH17‐1 expression is down‐regulated during the biotrophic phase of infection and up‐regulated during the necrotrophic phase. Deletion of CfGH17‐1 in C. fulvum did not reduce virulence on tomato, while constitutive expression of CfGH17‐1 decreased virulence, suggesting that abundant presence of CfGH17‐1 during biotrophic growth may release a DAMP that activates plant defence responses. Under natural conditions CfGH17‐1 is suggested to play a role during saprophytic growth when the fungus thrives on dead host tissue, which is in line with its high levels of expression at late stages of infection when host tissues have become necrotic. We suggest that CfGH17‐1 releases a DAMP from the host cell wall that is recognized by a yet unknown host plant receptor.